Optimazition of Payment System Through My Al- Badar Application at Al-Badar Islamic Boarding School Bilalang, Parepare - Arjun; Syahriah Semaun; Hansa; Darnawati; Damirah (Universitas Muhammadiyah Palu, 2024)
Optimization of the payment system can be achieved with the satisfaction of more and more users, which will affect the level of application of various payment systems as well as have an impact on related parties. If it is related to this research, then in the payment system to achieve goals and realization, It is necessary to prepare a more effective system for payment. The research method is descriptive qualitative, phenomenalogical approach, this type of research is Field research. The data sources used are primary data in the form of direct interviews with santri guardians of My Al-Badar application users and secondary data in the form of books, journals and articles related to the topic discussed. The results of this study are (1) payment system through My Al-Badar application, (2) Supporting factors and inhibiting factors in optimizing the payment system through My Al-Badar application. The use of the My Al-Badar application can be said to have run optimally, this can be seen from the payment transactions using the application by delaying the santri guardians in making payments. The Al-Badar boarding school is currently trying to conduct socialization to use the My Al-Badar application for transactions at the boarding school.